The comparison between the results of treatment of patients after ACL reconstruction using double-folded semitendinosus and gracilis tendons and quadruple-folded semitendinosus tendon - Piotr Piech; Paweł Polak; Karolina Rasoul; Maciej Kozioł; Jacek Gągała; Tomasz Mazurkiewicz; Tytus Tulwin; Robert Łuczyk (Kazimierz Wielki University, 2017)
Introduction. Injuries of knee are considered as a significant clinical issue according to difficulties in diagnostics, therapy and rehabilitation of patients. One of the most common pathologies are injuries of anterior cruciate ligament (ACL), which represent  around 90% of all damages. There are four basic mechanisms of ACL injury, but the most common are sudden hyperextension and internal rotation of the lower leg outside the physiological range of movements. Breaking of ACL in young and active people is undisputable indication for surgery - failure to do so leads to further damages of menisci and to osteoarthritis. Purpose of research. The aim of this study was to compare the long-term outcomes of ACL reconstruction with the use of the technique of double-folded tendons of semitendinosus and gracilis musles and quadruple-folded tendon of semitendinosus muscle. Materials and methods. A retrospective study consisted of two stages. The results of the post-reconstructive knee rehabilitation opinion survey and postoperative records were analyzed. The study examined 46 patients aged 19-59 years, hospitalized in the Department of Orthopedics and Traumatology SPSK4 in Lublin. Results. In order to better visualize the results, the patients were divided into four groups, depending on the KOOS score. Statistically significant, in favor of double-folded tendons of semitendinosus and gracilis muscles, were patient's assessments of the condition in two categories: presence and severity of pain and specific symptoms. The statistically insignificant result was obtained for the parameters: the possibility of active sports, the effects on daily activities and the general quality of life. Conclusions. The relationship between the technique used and the patient experiencing pain and specific symptoms was found. Patients undergoing surgery using double-folded semitendinosus and gracilis muscles experienced lesser symptoms.